Upaya pencegahan penyebaranan Covid- 19 melibatkan peran kader/rt/rw di kabupaten bekasi tahun 2020 - Mila Sartika (Indonesian Institute For Counseling, Education and Therapy, 2021)
COVID-19 is currently a global problem, categorized as a global pandemic. One of the prevention steps is to comply with the health procedures, involving the participation of cadres in the community. Cadre is a person or group of people who are fostered by a management agency in an organization. The purpose of PKM is to minimize the risk of spreading COVID-19 in the community. The PKM method provides education